First Clues in Fragile Lives: Can Early Biomarkers Transform Neonatal Sepsis Detection? A Retrospective Analysis - REHMAN, ASIF UR; AMINA ASAD; MALAIKA JAMAL; MALIK MUHAMMAD KABIR; ABDUL REHMAN SHAHID; ABDULLAH SHAHID (Pakistan Journal of Medical & Health Sciences, 2025)
Objectives: This retrospective study aimed to evaluate the diagnostic accuracy of C-reactive protein (CRP), procalcitonin (PCT), and presepsin for the early detection of neonatal sepsis by assessing their sensitivity, specificity, positive predictive value (PPV), and negative predictive value (NPV) in a tertiary care neonatal unit. Methodology: Conducted at the Neonatal Unit of the Pediatrics Department at Pakistan Institute of Medical Sciences (PIMS) Hospital, Islamabad, Pakistan, from May 2024 to May 2025, the study included 80 neonates (44 with confirmed sepsis, 36 without sepsis), determined by a sample size calculation based on a 36.41% sepsis prevalence, 95% confidence level, and 10% margin of error. Data were extracted from medical records, focusing on biomarker levels (CRP, PCT, presepsin) measured within 24 to 48 hours of sepsis suspicion, with analysis performed using SPSS software and Receiver Operating Characteristic (ROC) curves. Results: The cohort comprised 65% late preterm and 51.2% low birth weight neonates, with 55% diagnosed with sepsis. Mean biomarker levels were higher in septic neonates (CRP: 10.54 ± 1.88 mg/L, PCT: 0.68 ± 0.15 ng/mL, presepsin: 249.3 ± 20.5 pg/mL) compared to non-septic controls (CRP: 8.08 ± 1.11 mg/L, PCT: 0.51 ± 0.13 ng/mL, presepsin: 216.11 ± 21.01 pg/mL). Presepsin showed the highest diagnostic accuracy (AUC 0.865, sensitivity 95.5%, NPV 90.0%), followed by CRP (AUC 0.860, sensitivity 93.2%) and PCT (AUC 0.783, sensitivity 97.7%, but specificity 22.2%). Conclusion: Presepsin, CRP, and PCT are effective biomarkers for early neonatal sepsis detection, with presepsin offering the best diagnostic profile. A multi-biomarker approach could enhance clinical decision-making and reduce antibiotic overuse in resource-limited settings, necessitating further multicenter validation.